Caracterización de los eventos adversos notificados en pacientes hospitalizados en unidades críticas y básicas de un hospital universitario en Chile - Villaleiva C., Silvana; Sakurada Z., Andrea; Mena V., Sandra; Quintana C., Magyolue; Salazar C., Carolina; Vidal C., Mario; castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2024)
Aim: To characterize the AEs reported in hospitalized patients. Material and methods: An observational, descriptive study. Incidents reported during the year 2021 were analyzed, selecting adverse and sentinel events that occurred in general wards and critical care units, sociodemographic (sex, age) and clinics information (type of AE, working hour, place of occurrence) of affected patients. Results: The adverse events reported in the period were 1.319, 5,4% in 18.075 discharges. In the areas to be analyzed, 989 incidents were reported in 746 patients, 85.9% adverse events and 14,1% to sentinel events; 71,5% affected critical units, 60% affected males. Patient harm occurred in 75% of the cases. The age range most affected in basic units is over 80 years and in critical units in the range of 45-64 years. The main events reported are pressure injuries, 69,1% of all reported events, mainly affecting critically ill patients with rates of 80,8%, followed by self-withdrawals devices 7,6%, followed by medication error 6%. The profession that notifies the most is nursing, 59,4% were informed before the notification to the family. Conclusions: Our results show a greater occurrence of AE in critical areas, consistent with the literature, under-reporting from the physicians and infection control area.